Article Omission in Dutch Children with SLI: A Processing Approach - Lizet van Ewijk; Sergey Avrutin (Entropy, 2010)
Children with Specific Language Impairment (SLI) show difficulties with grammatical morphology. Based on the data from 12 Dutch children with SLI, an information-theoretical model is proposed in which the noun-article set dependency is modeled as a channel. We propose that reduced capacity of this channel is responsible for article omission. The Kullback-Leibler divergence between input and output distribution of article production provides an index of the channel capacity, which is shown to correlate with the percentage of article omission and to lag behind in SLI development as compared to typically developing children.